Clinical Profile and Prognosis of a Real-World Cohort of Patients With Moderate or Severe Cancer Therapy-Induced Cardiac Dysfunction - Esteban-Fernández, Alberto; Carvajal Estupiñan, Juan Fernando; Gavira-Gómez, Juan José; Pernas, Sonia; Moliner, Pedro; Garay, Alberto; Sánchez-González, Álvaro; Fernández-Rozas, Inmaculada; González-Costello, José (Frontiers in Cardiovascular Medicine, 2021)
Introduction and objectives: Cancer therapy-related cardiac dysfunction (CTRCD) is a common cause of cancer treatment withdrawal, related to poor outcomes. Cardiac-specific treatment could recover left ventricular ejection fraction (LVEF). We analyze the clinical profile and prognosis of patients with CTRCD in real-world scenario. Methods: Retrospective study, including all cancer patients diagnosed with CTRCD, defined as LVEF<50%. We analyzed cardiac and oncologic treatments, predictors of mortality and LVEF recovery, hospital admission, and causes of mortality (cardiovascular, non-cardiovascular, and cancer-related). Results: We included 113 patients (82.3% women, age 49.2±12.1 years). Breast cancer (72.6%) and anthracyclines (72.6%) were the most frequent cancer and treatment. Meantime to CTRCD was 8 months, with mean LVEF of 39.4±9.2%. At diagnosis, 27.4% of patients were asymptomatic. Cardiac-specific treatment was started in 66.4% of patients, with LVEF recovery-rate of 54.8%. Higher LVEF at time of CTRCD, shorter time from cancer treatment to diagnosis of CTRCD, and younger age were predictors of LVEF recovery. Hospitalization rate was 20.4% (8.8% linked to heart failure). Treatment with trastuzumab and lower LVEF at diagnosis of CTRCD were predictors of mortality. With a follow-up of 26 months, 30.9 % of patients died, being non-cardiovascular causes and cancer-related more frequent than cardiovascular ones. Conclusions: Cardiac-specific treatment achieves LVEF recovery in more than half of patients. LVEF at CTRCD´s diagnosis, age, and time from cancer treatment initiation to CTRCD were predictors of LVEF recovery. Cardiovascular-related deaths were less frequent than non-cardiovascular ones. Trastuzumab treatment and LVEF at the time of CTRCD were predictors of mortality.